Potential leveraged buyout of dermapharm holding se: investment thesis - Kurth, Jonas Maria (2022)
The following paper focuses on the development of an investment committee paper for the potential leveraged buy out of Dermapharm Holding SE, a German developer, producer, and distributor of niche prescription and over-the-counter pharmaceuticals. The individual part of the paper focuses on an investment thesis and a respective value creation strategy. Qualitatively, it evaluates the key investment highlights of the company, which translate in to a distinct value creation strategy that nurtures growth by levering sixe valuated growth drivers. Quantitatively, it assesses the impact of each growth driver on the total value creation of thec ase.